Ataque e contra-ataque: o jornalismo esportivo televisivo sob a perspectiva de duas trajetórias profissionais - Almeida, Edney Mota (2009)
The entail - or not - about to the journalist job to the merchandising with the marketing and propaganda, has making many discussions in the last times. With the advanced of the publicity and the marketing in many entertainment areas and the editorials journalisms, the opened TV in Brazil does not resist the constant investments of the publicity money designed to their programs. The sort "round sportive table" looks to be the privilege focus where you may verify these kinds of things. The television companies (tv senders) use their famous presenters to make easiest to get financial recourses. However a part of the journalistic c1ass doesn't accept and resists articulating its jobs with the publicity and the merchandising. After the and of the 1990 decade this discussion increase and the more resistant journalists to be as a "merchandising boy" lost their spaces in the opened tvs that show the sort "round sportive table". Only those professionals whose have accepted the new economic order and the marketing imposition would continuous in their functions. In some analyses made, excepting by the Globo and Cultura TVs (the first one because it doesn't have in their exhibition the sort program named "round sportive table" and the second because it has a character of a public tv ) the other opened tvs - Rede TV, Bandeirantes TV and Gazeta TV - have adopted this articulation between the both languages, journalistic and publicity,. ln this context, this dissertation has the objective to presents, the historicity of the "round sportive table" on the tv, between Rio - São Paulo, as well a critical observation about the insertion of the merchandising in this kind of tv show. It had evaluated an hypothesis that exists two "schools" of sportive journalisms and for that , make the analysis of the professional trajectory profile of the following journalists: Milton Neves, as well a publicist and Juca Kfouri outstanding journalist because bis militant position ahead of the denunciations of irregularities in the world of the sport. The research grew with the method of for the Critical Analysis, with theoretical approach based in the area of the Social Sciences by sociologist Pierre Bourdieu ideas; in the Theory of Communication, of journalist Eugenio Bucci; in the Political Theory, of Antonio Gramsci in what he refers to the study of the process of symbolic fights in the midia field while social phenomena. They are gatered like this and discussed the authors different texts, among other that they dialogue with the interviewees of this work, in order to if they obtain knowledge on the discussion in subject